A Miniaturized Loaded Open-Boundary Quad-Ridge Horn with a Stable Phase Center for Interferometric Direction-Finding Systems - Zibin Weng; Chen Liang; Kaibin Xue; Ziming Lv; Xing Zhang (Micromachines)
In order to achieve high accuracy in interferometric direction-finding systems, antennas with a stable phase center in the working bandwidth are required. This article proposes a miniaturized loaded open-boundary quad-ridge horn (LOQRH) antenna with dimensions of 40 mm × 40 mm × 49 mm. First, to stabilize the phase center of the antenna, the design builds on the foundation of a quad-ridge horn antenna, where measures such as optimizing the ridge structure and introducing resistive loading were implemented to achieve size reduction. Second, electrically small-sized antennas are more susceptible to the effects of common-mode currents (CMCs), which can reduce the symmetry of the radiation pattern and the stability of the phase center. To avoid the generation of common-mode currents during operation, a self-balanced feed structure was introduced into the proposed antenna design. This structure establishes a balanced circuit and routes the feedline at the voltage null point, effectively suppressing the common-mode current. As a result, the miniaturization of the LOQRH antenna was achieved while ensuring the suppression of the common-mode current, thereby maintaining the stability of the antenna’s electromagnetic performance. The measured results show that the miniaturized antenna has a small phase center change of less than 20.3 mm within 2–18 GHz, while the simulated phase center fluctuation is only 14.6 mm. In addition, when taking 18.5 mm in front of the antenna’s feed point as the phase center, the phase fluctuation is less than 22.5° within the required beam width. Along with the desired stable phase center, the miniaturized design makes the proposed antenna suitable for interferometric direction-finding systems.